Neurological and Orthopedic Diseases in Dogs and Cats Submitted to Physiotherapy - Colveiro, Ana Caroline; Rauber, Júlia Silva; Ripplinger, Angel; Wrzesinski, Mathias; Schwab, Marcelo Luís; Pigatto, Alessandra; Ferrarin, Dênis Antonio; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2020)
Background: The goals of physical therapy are to maximize functional recovery, improve mobility, and restore well-being and quality of life. In the veterinary literature, there is a dearth of data on physical therapy in small animal practice. Therefore, this study aimed to identify the main neurological and orthopedic diseases in canine and feline patients seen at the physical therapy service of an animal hospital. Concomitantly, we collected demographic and clinical information on patients, including sex, breed, physical therapy modalities, number and frequency of physical therapy sessions, duration of treatment, and rate of functional recovery. Materials, Methods & Results: The records of animals with neurological and orthopedic diseases seen at the Physical Therapy department of a university-affiliated animal hospital were reviewed. The animals were divided into two groups: I) dogs and cats with neurological diseases and II) dogs and cats with orthopedic diseases. Both groups were distributed according to species, age, sex and race. Dogs and cats were classified into three age groups: puppies (≤ 1 year old), adults (> 1 year and ≤ 10 years old) and elderly (> 10 years old). A total of 384 records were retrieved, of which 370 (96.4%) were of dogs and 14 (3.6%) of cats. Neurological cases accounted for 66% of the total (n = 253), with 243 cases in dogs (96%) and 10 in cats (4%). Among orthopedic cases (n = 131, accounting for the remaining 34%), 127 were in dogs (97%) and only 4 in cats (3%). In the neurological dysfunction group, intervertebral disc disease (72.4%) was the most common diagnosis. Among the orthopedic disorders, femur fracture (23.1%) was most prevalent. In group I (neurological), 66.7% of outcomes in canine patients and 44.4% in felines were considered satisfactory. In group II (orthopedic), 61% of outcomes in dogs and 66.7% in cats were considered satisfactory. Discussion: Physical therapy has many applications in small-animal practice. After spinal cord decompression surgery in dogs with IVDD, for instance, it helps maintain and recover motor and sensory function, and is considered safe and well-tolerated in dogs after thoracolumbar hemilaminectomy with disc fenestration. Physical therapy also plays an important role after surgical repair of fractures and dislocations, aiding recovery of range of motion and return to functional activity. The most probable explanation for the wide variation in number of physical therapy sessions can be explained by owners’ satisfaction with the level of recovery achieved by the animal, often leading to discontinuation of physical therapy. The high rate of unsatisfactory outcomes in feline patients can be explained by the type of injury (spinal trauma) and the degree of neurological dysfunction. Adult female dogs were most likely to be referred to the physical therapy sector, and the Dachshund and Poodle breeds were most prevalent. Patients in the neurological dysfunction group had the highest average duration and number of sessions. Massage, stretching, passive joint mobilization, and neuromuscular electrical stimulation (NMES) were the most commonly used modalities in all physical therapy protocols. Satisfactory functional recovery was achieved in more than 60% of cases in both groups. The absence of a control group and the lack of standardization of physical therapy modalities precluded a more definitive confirmation of the results obtained in terms of functional recovery.